A simple hand‐held magnet array for efficient and reproducible SABRE hyperpolarisation using manual sample shaking. (3rd January 2018) - Richardson, Peter M.; Jackson, Scott; Parrott, Andrew J.; Nordon, Alison; Duckett, Simon B.; Halse, Meghan E.
Abstract : Signal amplification by reversible exchange (SABRE) is a hyperpolarisation technique that catalytically transfers nuclear polarisation from parahydrogen, the singlet nuclear isomer of H2, to a substrate in solution. The SABRE exchange reaction is carried out in a polarisation transfer field (PTF) of tens of gauss before transfer to a stronger magnetic field for nuclear magnetic resonance (NMR) detection. In the simplest implementation, polarisation transfer is achieved by shaking the sample in the stray field of a superconducting NMR magnet. Although convenient, this method suffers from limited reproducibility and cannot be used with NMR spectrometers that do not have appreciable stray fields, such as benchtop instruments. Here, we use a simple hand‐held permanent magnet array to provide the necessary PTF during sample shaking. We find that the use of this array provides a 25% increase in SABRE enhancement over the stray field approach, while also providing improved reproducibility. Arrays with a range of PTFs were tested, and the PTF‐dependent SABRE enhancements were found to be in excellent agreement with comparable experiments carried out using an automated flow system where an electromagnet is used to generate the PTF. We anticipate that this approach will improve the efficiency and reproducibility of SABRE experiments carried out using manual shaking and will be particularly useful for benchtop NMR, where a suitable stray field is not readily accessible. The ability to construct arrays with a range of PTFs will also enable the rapid optimisation of SABRE enhancement as function of PTF for new substrate and catalyst systems. Abstract : We describe a hand‐held magnet array for signal amplification by reversible exchange (SABRE) experiments that provides a consistent polarisation transfer field (PTF) during the manual shaking of the sample. Several arrays with PTFs of tens of gauss were constructed and found to provide increased 1 H NMR signal enhancement over both stray field shaking and an automated flow approach using an electromagnet. In addition, the arrays enable the PTF‐dependence of the SABRE enhancement to be measured using an efficient manual approach.